Caracterização das atividades produtivas realizadas pelos agricultores familiares do assentamento Alecrim, em Selvíria-MS - Laluce, Cícero Rogério Henrique [UNESP] (2013)
The rural settlement policy despite the many mishaps of the process is a reality in Brazil, in some regions it has become the most important instrument of occupation of areas, taking thousands of families to the field, as in Pontal do Paranapanema in the State of São Paulo and the region of Sidrolândia, Mato Grosso do Sul. Despite the low production in most plots, other aspects of the day to day life of families have shown that the reproduction of life in these areas is not only the direct dependence of production systems. In our view, t's not possible to discuss life in the field, from the perspective of family farming, without putting the aspect of production at the center of analysis, because this form of agriculture was the base of support for the process of development and food sovereignty of various countries now considered developed and in Brazil, up to this day ,is responsible for a big part of the food brought to the table of the population. In this work we analyze the specific case of the Assentamento Alecrim (Rosemary Settlement) in Selvíria (MS), the reasons that led families to go to the Settlement, the choice of productive activities, how the evolution of such activities occured over time, which factors that have influenced its development and importance of production and other factors in the process of consolidation of that Settlement. The survey was conducted in 2013, with 40% of the settled families, using a questionnaire containing 48 questions for data collection. The investigation also included the literature from books and scientific articles, and documentary research. The analysis was based on data tabulation of research questionnaires and their comparison with data from ISEV / INCRA, conducted in 2008, and the results of the socioeconomic questionnaire, applied to the elaboration of the P.D.A. in 2009. It was observed that the main motivation that led families to the ...